how to factorise y(y^-2y)+2(2y-y^)-2+y

Dear student
Your question is incomplete.So, assuminng your question asyy2-2y+22y-y2-2+y=yy2-2y-2y2-2y+y-2=y2-2yy-2+y-2=y-2y2-2y+1=y-2y2-y-y+1=y-2yy-1-1y-1=y-2y-1y-1=y-12y-2
Regards

  • 6
Hello Aditya, given can be rearranged as
y ( y^2 - 2 y ) - 2 ( y^2 - 2 y ) + ( y - 2)
Taking y^2 - 2y as common from the first two terms we have
(y^2 - 2 y) ( y -2) + ( y -2)
Now y-2 could be taken as common factor
So we get (y -2) ( y^2 - 2 y + 1 )
Or (y - 2) ( y - 1)^2
  • 1
What are you looking for?